Why Vienna gets high marks (Volume 2) - Löw, Jana; Antalovsky, Eugen (European Investment Bank, 2018)
This essay reviews the political circumstances and strategic orientations of Vienna's comprehensive urban development policy, and how the EIB's investments facilitated key projects and supported Vienna's process of urban modernisation. Urban development in Vienna took place in four cycles, which are characterised by distinctive internal and external conditions and opportunities. Each prompted different levels of EIB engagement.